Active Forms and Teaching Methods in Biology Lessons - Urazova Ra’no Stanislavovna; Surayyo Radjabova (Genius Journals, 2022)
Active learning aims to organize comfortable learning conditions in which all students take an active part in the lesson. The use of active methods by the teacher in his lessons speaks of his innovative activity. The organization of active learning involves the modeling of life situations, the use of role-playing games, the general solution of issues based on the analysis of circumstances and situations, the penetration of information flows into the mind, which cause its vigorous activity. The purpose of the article is to identify and scientifically substantiate the possibilities of using active forms and methods of teaching in the classroom and in extracurricular work in biology lessons at the university.
Keywords: Active learning model; active technologies; discussions